Design and realization of transparent solar modules based on luminescent solar concentrators integrating nanostructured photonic crystals. (23rd April 2015) - Jiménez‐Solano, Alberto; Delgado‐Sánchez, José‐Maria; Calvo, Mauricio E.; Miranda‐Muñoz, José M.; Lozano, Gabriel; Sancho, Diego; Sánchez‐Cortezón, Emilio; Míguez, Hernán
Abstract: Herein, we present a prototype of a photovoltaic module that combines a luminescent solar concentrator integrating one‐dimensional photonic crystals and in‐plane CuInGaSe2 (CIGS) solar cells. Highly uniform and wide‐area nanostructured multilayers with photonic crystal properties were deposited by a cost‐efficient and scalable liquid processing amenable to large‐scale fabrication. Their role is to both maximize light absorption in the targeted spectral range, determined by the fluorophore employed, and minimize losses caused by emission at angles within the escape cone of the planar concentrator. From a structural perspective, the porous nature of the layers facilitates the integration with the thermoplastic polymers typically used to encapsulate and seal these modules. Judicious design of the module geometry, as well as of the optical properties of the dielectric mirrors employed, allows optimizing light guiding and hence photovoltaic performance while preserving a great deal of transparency. Optimized in‐plane designs like the one herein proposed are of relevance for building integrated photovoltaics, as ease of fabrication, long‐term stability and improved performance are simultaneously achieved. © 2015 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : Herein, we realize an in‐plane integrated design for a photonic crystal‐enhanced luminescent solar concentrator module in which solar cells, dyed layer and multilayered mirrors are sealed and protected inside the module. The structural and optical characteristics of the mirror (left electron microscopy image) and its location in the module have been devised to optimize its integration, maximize both light absorption of incoming light and guiding of emitted radiation towards the coplanar cells and preserve transparency (right picture) aiming at building integration applications..